PENERAPAN TEORI PLANNED BEHAVIOR DALAM MEMPREDIKSI INTENSI BERKUNJUNG DI OBYEK WISATA PASAR MALAM, KOTA KUPANG - Jehane, Protasius Tiberius (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2019)
This study aims at exploring the behavioral intention of local tourist in Kupang City to choose Pasar Malam as their culinary tourism destination. The Theory of Planned Behavior theories have been chosen as the theoretical basis of the study.Prior to conducting a questionnaire survey, a pilot survey was conducted to test the questionnaire’s reliability. The final survey was conducted with 103 visitors during their visitation in Pasar Malam. Findings: Results obtained from the respondents allowed to test the hypotheses proposed in the study. A multiple regression analysis was carried out in order to test the hypotheses and the study findings reveal the relationship among the variables. Results indicated that the attitude, subjective norm, and perceived behavioral control were found to be determinants of behavioral intention. In addition, perceived behavioral control became the most significant influence behavioral intention. The implications of the study findings are discussed.